Encyclopedia of Life Sciences 2010
DOI: 10.1002/9780470015902.a0006019.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Tay–Sachs Disease

Abstract: GM2 gangliosidosis is a family of three diseases that include Tay–Sachs disease (described over a century ago), Sandhoff disease and the AB‐variant form, reflecting the need of three gene products to hydrolyse GM2 ganglioside. The recent elucidation of the crystal structures these three proteins have provided a better understanding of the molecular basis of GM2 gangliosidosis. The discovery that most deleterious missense mutations affect the folding or the assembly of the heterodimeric enzyme, and that delays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Several different scaffolds of non-iminosugar GCase inhibitors have been reported as GCase pharmacological chaperones (PCs) since 2007 [12][13][14][15][16] (Figure 1). We found that a noninhibitory GCase PC NCGC00188758 217 can enhance GCase activity specifically within the lysosomal compartment, reduce GluCer and hexosylsphingosine substrates, and subsequently enhance the clearance of pathological α-synuclein 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Several different scaffolds of non-iminosugar GCase inhibitors have been reported as GCase pharmacological chaperones (PCs) since 2007 [12][13][14][15][16] (Figure 1). We found that a noninhibitory GCase PC NCGC00188758 217 can enhance GCase activity specifically within the lysosomal compartment, reduce GluCer and hexosylsphingosine substrates, and subsequently enhance the clearance of pathological α-synuclein 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Tay Sachs (TSD, OMIM #272800) and Sandhoff (SD, OMIM #268800) diseases are lysosomal storage disorders (LSD) known as GM2 Gangliosidosis. They are autosomal recessive disorders caused by mutations in HEXA or HEXB genes, which encode for the α-or β-subunits, respectively, of the human lysosomal β-N-acetylhexosaminidases (Hex, EC 3.2.1.52) A, B, or S [1,2]. TSD and SD are clinically indistinguishable, except that in SD central nervous system (CNS) and visceral organs are affected, whereas in TSD only the CNS is impaired.…”
Section: Introductionmentioning
confidence: 99%
“…However, in SD the central nervous system (CNS) and visceral organs are affected, whereas in TSD only the CNS is impaired. Patients' lifespan varies from 1 to 5 years in the severe infantile form, to late teens for patients with the juvenile form; while it is still unclear if there is a reduction in the lifespan for the late‐onset patients with the disease (Cachon‐Gonzalez, Zaccariotto, & Cox, 2018; Gravel et al, 2001; Tropak & Mahuran, 2010).…”
Section: Introductionmentioning
confidence: 99%